ANALYSIS OF CONTACT RELATIONS VERB IN LEXICAL AND SEMANTIC FIELD - Shermatova Nigora Isoqulovna (Journals Park Publishing, 2022)
The article examines the verbal vocabulary expressing contact relations; the semantic structure of verbs is determined; the types of semantic changes in the semantic structure of word forms functioning in the context are established; the conclusion is made about the patterns of verb use.
Keywords: contact relations verbs, semantic structure, semantic field, verb groups, analysis of verb lexemes.